Kinematic distributions and nuclear effects of J/ψ production in 920 GeV fixed-target proton-nucleus collisions - Abt, I.; Adams, M.; Agari, M.; Albrecht, H.; Aleksandrov, A.; Amaral, Vasco; Amorim, Antonio; Aplin, S. J.; Aushev, V.; Bagaturia, Y.; Balagura, V.; Bargiotti, M.; et al. (European Physical Journal C, 2009)
Measurements of the kinematic distributions of J/ψ mesons produced in p-C, p-Ti and p-W collisions at sqrts=41.6∼GeV in the Feynman-x region -0.34